Causes of The Alarming Rise of False Sexual Allegations Against Teachers in South African Schools - Thobile Perseverance Madonsela; Bunmi Isaiah Omodan; Cias T Tsotetsi (JETL (Journal of Education, Teaching and Learning), 2022)
False sexual allegations against teachers have contributed to teachers leaving the profession early and a decline in males choosing the profession. The main focus of this study was to investigate learners' false allegations of sexual misconduct against teachers.  This study was underpinned by Fabricated Rape Theory and adopted qualitative methodology data through semi-structured interviews. Four teachers, one deputy principal, and one principal making six participants in the South district of the Gauteng province of South Africa were selected using convenient selection methods.  The collected data were analysed using the Thematic Analysis method, which enables the researcher to respond to the study's objectives one after the other. The study revealed that fear, emotional neglect, and revenge contribute to false sexual allegations against teachers and that the maintenance of professional conduct among teachers and policy change are the possible solutions. Therefore, the study recommends that students should be provided with adequate orientation and re-orientation about the implication of false allegations, that teachers should always maintain good conduct, and that there should be an improvement in school policies and code of conduct to include punishable consequences for false accusations.